Invisible game : the secrets and the science of winning minds and winning deals - Mueller, Kai-Markus; Rehbock, Gabriele (John Wiley & Sons, Inc., 2022)
Cutting-edge science can make all the difference for salespeople in a time when they are facing a business world in transformation. In The Invisible Game: The Secrets and the Science of Winning Minds and Winning Deals, neuroscientist Kai-Markus Mueller and sales professional Gabriele Rehbock deliver a hands-on guide to the hidden dynamics that influence the outcomes of most business deals. In plain English, the book unpacks recently discovered insights from psychology, behavioural economics, and neuroscience and explains how to apply them to your advantage in real-life business situations. The authors show you how to influence buying decisions and how to successfully respond to challenging business situations in order to put you in control of the levers that drive sales success. You'll also find Advanced strategies and tactics that offer a lasting edge in negotiations, sales and other business transactions Smart techniques to build rewarding customer relationships The psychology behind gains and losses revealing new keys to profitable pricing Real-life advice on how to counter a buyer's intimidation tactics: time, uncertainty, fear, and silence An essential, step-by-step playbook for sales professionals, The Invisible Game will also earn a place on the bookshelves of entrepreneurs, business owners, and other independent professionals--like lawyers, accountants, freelancers, consultants, and programmers--who regularly sell their services to other businesses.